Sound absorption performance of the acoustic absorber fabricated by compression and microperforation of the porous metal. (5th April 2019) - Bai, Panfeng; Yang, Xiaocui; Shen, Xinmin; Zhang, Xiaonan; Li, Zhizhong; Yin, Qin; Jiang, Guoliang; Yang, Fei
Abstract: Novel acoustic absorbers were fabricated by the compression and microperforation of the porous metal, which aimed to develop practical acoustic absorbers for the noise reduction. Sound absorbing coefficients of the five investigated acoustic absorbers were measured by the AWA6128A detector according to the standing wave method, and their trends were consistent with normal sound absorption principle of the porous metal absorber and that of the microperforated panel absorber. The results proved that with same length of the cavity, sound absorption performance could be obviously improved by the compression and microperforation. When length of the cavity was 20 mm, average sound absorbing coefficient of the compressed and microperforated porous metal panel absorber in frequency range 100–6000 Hz reached 59.69%, which was superior to that 25.70% of original porous metal absorber and that 31.49% of the microperforated spring steel panel absorber. In the constructed semi-empirical model, a fourth-order polynomial function was treated as the coupling function to express the superposition absorption effect, and its veracity and reliability was validated by two replication experiments. Micromorphology of the compressed and microperforated porous metal panel provided the intuitive explanations to the improvement of its sound absorption performance. Graphical abstract: Unlabelled Image Highlights: Novel acoustic absorber was developed for better sound absorption by compression and microperforation of porous metal. The compressed and microperforated porous metal panel absorber could achieve better sound absorbing coefficient. The constructed semi-empirical model was validated to achieve optimal acoustic absorber by two replication experiments. Micromorphology of the proposed acoustic absorber gave intuitive explanations for its sound absorption performance.